FIGURATIVE LANGUAGE IN ADELE’S SELECTED SONG LYRICS - Edyawati, Siska; Rufinus, Albert; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The research was conducted to identify and analyze figurative language (personification, metaphor, hyperbole and paradox) in Adele’s selected song lyrics. They are covered with two types of figurative language, comparative (personification and metaphor) and contradictive (hyperbole and paradox). The research used descriptive qualitative method. Procedure of analysis were firstly looking for Adele’s song lyrics from the website Azlyrics.com, secondly reading and copying the lyrics, thirdly identifying the sentences or phrases which have figurative language, fourthly describing about figurative language that was taken, and lastly giving conclusion. The research identified twenty five figurative languages in song lyrics.There are eight lines identified as personification, eleven lines identified as metaphor, three lines identified as hyperbole, and four lines identified as paradox. In conclusion, the dominant figurative language is metaphor, which is included into comparative figurative language. Keywords: Figurative Language, Adele’s Song Lyrics Abstrak: Penelitian ini bertujuan untuk mengidentifikasi dan menganalisa gaya bahasa (personifikasi, metafora, hiperbola dan paradoks) dalam lirik-lirik lagu terpilih Adele. Gaya bahasa ini terbagi ke dalam dua tipe, yaitu perbandingan (personifikasi dan metafora) dan pertentangan (hiperbola dan paradoks). Penelitian ini menggunakan metode deskriptif kualitatif. Prosedur analisa nya ialah pertama mencari lirik lagu Adele dari situs Azlyrics.com, kedua membaca dan menyalin lirik lagu tersebut, ketiga mengidentifikasi kalimat-kalimat atau frasa-frasa yang mengandung gaya bahasa, keempat mendeskripsikan tentang gaya bahasa yang telah didapat, dan terakhir memberikan kesimpulan. Penelitian ini mengidentifikasi dua puluh lima gaya bahasa yang terdapat dalam lirik lagu. Terdapat delapan baris yang diidentifikasi merupakan gaya bahasa personifikasi, sebelas baris merupakan gaya bahasa metafora, tiga baris merupakan gaya bahasa hiperbola, dan empat baris merupakan gaya bahasa paradoks. Kesimpulannya, gaya bahasa yang paling sering digunakan adalah metafora yang termasuk ke dalam gaya bahasa perpandingan. Kata kunci: Gaya bahasa, Lirik-Lirik Lagu Adele